Big Data-Based Access Control System in Educational Information Security Assurance. (17th January 2022) - Peng, Zhong; Liang, Feng; Mu, Lili
Abstract : Access control is a key strategy to prevent and protect the network. The most important task is to ensure that visitors will not use network resources and will not conduct unauthorized access to them. This paper studies a number of information security issues in the process of education informatization, aimed at studying the application of access control systems based on big data in education information security. This article elaborates on the related concepts of access control and proposes an attribute-based encryption scheme. Based on this, an information system security system model with security strategy as the core content is constructed. The experimental results in this paper show that the improved access control system has the more efficient guarantee ability in education information security, which is about 47.3% higher than the traditional access control system.